2021
DOI: 10.1007/s42979-021-00755-w
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Deep Learning Side-Channel Attack on FPGA Implementation of AES

Abstract: Side-channel attacks have become a realistic threat to implementations of cryptographic algorithms, especially with the help of deep-learning techniques. The majority of recently demonstrated deep-learning side-channel attacks use a single neural network classifier to extract the secret from implementations of cryptographic algorithms. The potential benefits of combining multiple classifiers using the ensemble learning method have not been fully explored in the side-channel attack’s context. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Wang et al 27 suggested a Deep Learning Tandem Side Channel Attack on AES FPGA Implementation. By the use of deep learning methods, side‐channel attacks were a genuine danger to the execution of cryptographic algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al 27 suggested a Deep Learning Tandem Side Channel Attack on AES FPGA Implementation. By the use of deep learning methods, side‐channel attacks were a genuine danger to the execution of cryptographic algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…As it is possible for attackers to obtain access to physical equipment, the equipment itself must be equipped with cryptographic algorithms [1,2] in order to provide security not just against physical attacks but also against mathematical cryptanalysis. A security system [3,4] can be physically compromised by an attack known as a sidechannel attack.…”
Section: Introductionmentioning
confidence: 99%